Research progress on energy metabolism regulation in stored platelets - GAO Chengyan; LOU Can; LEI Hang; CAI Xiaohong (Zhongguo shuxue zazhi)
In maintaining normal function and activation processes, glycolysis, lipid metabolism, and amino acid metabolism play key roles in the energy demand of platelets. In the resting state, platelets primarily rely on glycolysis and aerobic oxidation to generate energy. Upon activation, platelets preferentially utilize glycolysis, as it can more rapidly provide the required ATP. In addition to glycolysis, platelets can also utilize glycogen and fatty acids as additional energy sources. The ATP provided by fatty acid oxidation is crucial for platelet activation. Additionally, during platelet storage, distinctive changes in energy metabolism occur. In the early stages of storage, platelets primarily rely on glycolysis and the pentose phosphate pathway (PPP) to generate energy. In the mid-storage phase, there is an increase in tricarboxylic acid cycle (TCA) metabolism. In the later stages of storage, cellular metabolism gradually declines. The regulation and flexibility of these metabolic pathways play a critical role in the survival and function of platelets in different states.